Los postreros aleteos de Fernando Rodríguez-Izquierdo Gavala - Suárez Japón, Juan Manuel (Mirai. Estudios Japoneses, 2025)
Fernando Rodríguez-Izquierdo y Gavala (Seville, 1937 – Seville, January 8, 2025), who earned a degree in Japanese Language and Culture from Sophia University in Tokyo, held a bachelor’s degree in philosophy and Letters, as well as in Hispanic Philology and Classical Philology, and a PhD from the University of Seville. He was one of the most important pioneers of Japanese studies in Spain. He lived in Japan for three and a half years and, after returning to Spain, worked as a Senior Lecturer in Hispanic Philology at the University of Seville (1975–2006). His doctoral thesis, The Japanese Haiku, marked the beginning of an extensive body of research on this subject, about which he published numerous works and gave countless lectures, presentations, and papers. He was the foremost haiku specialist in the Spanish-speaking world and its greatest promoter. In addition, he gifted us with outstanding translations, not only of haikus but also of numerous significant works by exceptional authors of both classical and contemporary Japanese literature.